Isolation and Immunofluorescent Staining of Fresh Rat Pia–Arachnoid Complex Tissue for Micromechanical Characterization. Issue 1 (13th September 2019) - Suar, Zeynep M.; Fabris, Gloria; Kurt, Mehmet
Abstract: In this article, we describe a protocol for the isolation and staining of fresh tissue of the inner rat meningeal layers, or pia–arachnoid complex (PAC). The PAC is believed to act as a mechanical damper offering a fundamental layer of protection against brain injury; however, its overall mechanical properties are still rather unexplored. In order to perform micromechanical measurements on the PAC, the tissue must be extracted and characterized while maintaining its native mechanical properties (i.e., avoiding any chemical or physical modification that could alter it). In light of this need, we developed a protocol for the immunofluorescent staining of fresh PAC tissue that does not require any fixation or permeabilization step. This approach will allow researchers to investigate important properties of the anatomy of ex vivo PAC tissue while at the same time offering a platform for the mechanical analysis of this complex material. © 2019 by John Wiley & Sons, Inc. Basic Protocol 1 : Isolation of fresh rat pia–arachnoid complex tissue Basic Protocol 2 : Fresh immunofluorescent staining of rat pia–arachnoid complex tissue Alternate Protocol : Adhesion of pia–arachnoid complex tissue to glass slides for micromechanical characterization